2017
DOI: 10.1177/0021998317701988
|View full text |Cite
|
Sign up to set email alerts
|

The influence of functionalization time of carbon nanotube on the mechanical properties of the epoxy composites

Abstract: This paper investigates the structure, length, and percentage of functional groups of multi-walled carbon nanotubes (CNT) depending on the time taken for functionalization in HNO3 and H2SO4 mixture. The carbon nanotube content and influence of functionalization time on mechanical properties of polymer composite materials based on epoxy matrix are studied. The extreme dependencies of mechanical properties of carbon nanotube functionalization time of polymer composites were established. The rise in tensile stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Adding CNT into epoxy matrices to enhance its properties and obtain a multifunctional material has already been deeply studied in order to analyze the thermal [ 2–4 ] and mechanical [ 2–6 ] properties of its polymeric nanocomposites. Furthermore, several works in the literature [ 7,8 ] have devoted themselves to the study of the curing kinetics of these systems aiming a better understanding of their functioning mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Adding CNT into epoxy matrices to enhance its properties and obtain a multifunctional material has already been deeply studied in order to analyze the thermal [ 2–4 ] and mechanical [ 2–6 ] properties of its polymeric nanocomposites. Furthermore, several works in the literature [ 7,8 ] have devoted themselves to the study of the curing kinetics of these systems aiming a better understanding of their functioning mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The absorption peaks detected in this part are in good accordance with reports in other studies. 16,23
Figure 1.FTIR spectra of various MWCNTs. FTIR: Fourier transform infrared spectroscopy; MWCNTs: multi-walled carbon nanotubes.
…”
Section: Resultsmentioning
confidence: 99%
“…The absorption peaks detected in this part are in good accordance with reports in other studies. 16,23 Figure 1 also indicates the FTIR spectra of aat-MWCNTs (i.e. aat-MWCNT-50).…”
Section: Titration Testmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that high temperature destroys the internal structure of the resin and weakens the intermolecular interaction. At the same time, the structure of CNTs can also support the mechanical properties of resin matrix . Effects of NPs on the thermal stability of resin matrix are shown in Table .…”
Section: Effect Of Nanoparticles On the Thermal Stability Of Resin Mamentioning
confidence: 99%